Performance Evaluation of IPv4 and IPv6 on IPsec/MPLS Enabled Network: A Case of Zambia - Mwape, Jessy Chisenga; Lubobya, Charles Smart (Transactions on Engineering and Computing Sciences, 2023)
This paper explores the performance of IPv4 versus that of IPv6 in an MPLS/IPsec enabled network for real time applications and non-real time applications. Major Internet Service Providers (ISP) in Zambia have implemented MPLS within their core networks in order to provide traffic engineering and Quality of Service and network efficiency, however, MPLS does not encrypt the data as it travels through the network. To mitigate this, customers using the public infrastructure to connect to their remote sites have implemented IPsec. This framework of related protocols protects one or more data flows between network peers, thus data confidentiality and integrity can be achieved. When MPLS is combined with IPsec both technologies can provide more security for enterprise WAN networks. However, most service providers and ISPs in Zambia and their Enterprise customers have implemented these technologies using Internet Protocol version Four (IPv4). As the number of devices requiring connectivity to the internet and core systems increases exponentially, the limited address space for IPv4 has reached exhaustion. This has prompted the Zambia Information and Communications Technology Authority (ZICTA) which is the statutory body for regulating Information and Communications Technology (ICT) in Zambia to include the development and implementation plan for migration from IPv4 to IPv6 in their 2022 to 2024 strategy. Once implemented, this strategy hopes to increase access and usage of ICT and postal services and increase the internet penetration rate from 60% to 70% by 2025. Based on Google’s statistics, the IPv6 adoption rates for Zambia is still at 0%. In order to analyze the penetration rates of IPv4 versus IPv6, a structured questionnaire has been administered on 30 ISP employees and 30 enterprise customer employees to access the use of IPv4 and IPv6 protocols in their MPLS/IPsec networks. The data simulation for Voice over Internet Protocol (VoIP), Video conferencing, and Email was done using Riverbed Modeler simulation software and observe the performance of IPv4 in comparison with IPv6 in terms of jitter, throughput and delay.